Importance of Service Quality Dimensions for Innovative Services in Service Industry - Aneet; Vinayak, Vishal (Gyan Management Journal, 2017)
Service sector is the lifeline for the social economic growth of a country. It is today the largest and fastest growing sector globally contributing more to the global output and employing more people than any other sector. The real reason for the growth of the service sector is due to the increase in urbanization, privatization and more demand for intermediate and final consumer services. Availability of quality services is vital for the well being of the economy as Customer have become more and more aware of their requirements and demand higher standards of services. The key lies in improving the services, paying attention to more critical service quality attributes which makes it difficult for the service provider to measure and manage services efficiently. This study has explored the relevant literature reviews to find out the services quality practices and improvement methods of the same in different service sectors. Study elaborates different elements of customer quality which plays an important role in service sector. The study also draws an attention towards internal service quality which in term affects customer satisfaction. Discussion on TQM, Quality Management Models Quality dimensions has been made. The determination of the study also provides a comprehensive understanding of quality management and its effective implementation for the betterment of the service sector.